Targeting glioblastoma. The potential of exosomes - Witkowski, Paweł; Wiśniewski, Karol; Bachurski, Patryk; Chmiel, Gabriela; Kalinowski, Paweł; Międlar, Maja; Muda, Martyna; Pacek, Szymon; Pierzga, Elisabetta; Zarański, Bartosz (Quality in Sport, 2026)
Background: Glioblastoma (GBM) is the most common and aggressive malignant primary brain tumor in adults and remains associated with a poor prognosis, with 5-year survival rates of only 4-7%. Even after surgery, radiotherapy and chemotherapy, the median survival rarely exceeds 12-16 months due to diffuse tumor infiltration, pronounced intratumoral heterogeneity and nearly inevitable recurrence. This therapeutic failure is caused in part by the blood-brain and blood-brain tumor barriers, which limit drug delivery and by glioma stem cells that sustain resistance and tumor regrowth. Aim: The aim of this work is to evaluate exosomes as a promising drug delivery platform that can overcome these physiological barriers and improve treatment results for patients with glioblastoma. Materials and methods: This analysis focuses on preclinical studies of engineered exosomes naturally secreted by various human cells. These nanoscale vesicles are studied as carriers for different types of therapeutic cargo, including chemotherapeutic drugs, nucleic acids and molecules that affect the immune system. The study examines how these vesicles are modified to target GBM cells directly. Results: The results show that due to their endogenous origin, exosomes exhibit high biocompatibility, low immunogenicity, intrinsic targeting properties and the ability to cross the blood-brain barrier, offering advantages over conventional synthetic nanocarriers. Preclinical data demonstrate that engineered exosomes increase the amount of drug that accumulates inside the tumor, leading to higher cytotoxicity and a better response from the immune system. While there are still challenges regarding large-scale manufacturing and safety, exosomes represent a powerful tool for the future of precision-targeted therapy in glioblastoma.